(untitled) (Stato, Chiese e pluralismo confessionale, 2023)
The long road after WWII until today (1944-2023): from the reinstatement of the rights denied to Jews victim of the racist laws of fascist Italy to recovering the Memory of the Holocaust to fight against prejudice and antisemitism ABSTRACT: This paper who served as a basis of the author’s speech at the official remembrance of the Holocaust at the residence of the President of the Republic of Italy (Quirinale palace) on 27 January 2023 examines the various phases of this process. First from 1944 to the mid-1980 the key element is the enactment of more that 90 pieces of legislation abrogating the antisemitic laws of 1938-45 and granting some compensation to the victims. In a second phase (until the end of the XX century) Judaism is recognized as religious entity with parity of rights as compared with the Catholic Church (the Agreement - “Intesa” - between the Italian State and the Union of Italian Jewish Communities of 1987) thus empowering Judaism in Italy to be an active and distinct contributor to Italy’s society. In that period the “Mancino law” of 1993 enacts criminal provisions to fight racism in Italy more effectively. The last phase from 2000 until to-day, witnesses, after the official recognition of the “Holocaust Remembrance Day” each 27 January (“Giorno della Memoria”) witnesses an engagement of Italian institutions to fight antisemitism through education and cultural initiatives. SOMMARIO: 1. La reintegrazione nei diritti negati: un processo lungo e faticoso (1944-1987) - 2. Dal completamento del disegno costituzionale con l’intesa tra Stato e Comunità ebraiche (1987-89) alla repressione del razzismo con la “legge Mancino” (1993) - 3. La riflessione sulla Shoah quale insegnamento per l’oggi: il Giorno della Memoria (2000) - 4. La strategia europea contro le discriminazioni e l’antisemitismo: protezione ed educazione - 5. La strategia e le iniziative italiane - 6. In conclusione.